Metastatic adult pancreatoblastoma: multimodal treatment and molecular characterization of a very rare disease - Berger, Anne Katrin; Mughal, Sadaf Shabbir; Allgäuer, Michael; Springfeld, Christoph; Hackert, Thilo; Weber, Tim; Naumann, Patrick; Hutter, Barbara; Horak, Peter; Jahn, Arne; Schröck, Evelin; Haag, Georg Martin; et al. (Pancreatology, 2020)
Background: Pancreatoblastoma is a rare malignancy that occurs predominantly in children. Less than 50 adult cases, including 17 patients with metastatic disease, have been published to date. Recent outcome data from children with advanced-stage disease suggest an intensive multimodal treatment approach; however, little is known about the most beneficial therapy in adults. Molecular characterization of pancreatoblastoma is limited to a small number of pediatric cases and revealed few recurrent genetic events without immediate clinical relevance. Methods: Patients were treated between 2013 and 2018 at a high-volume German university cancer center. Molecular analyses included whole genome, exome, transcriptome, and fusion gene panel sequencing. Molecularly guided treatment recommendations were discussed within a dedicated molecular tumor board (MTB) embedded in a precision oncology program (NCT MASTER). Results: We identified four adult patients with metastatic pancreatoblastoma. In three patients, local approaches were combined with systemic treatment. Oxaliplatin-containing protocols showed an acceptable tumor control as well as an adequate toxicity profile. Overall survival was 15, 17, 18 and 24 months, respectively. Three tumors harbored genetic alterations involving the FGFR pathway that included an oncogenic FGFR2 fusion. Conclusion: Oxaliplatin-containing chemotherapy seems to be a reasonable approach in adult patients with advanced pancreatoblastoma, whereas the benefit of intensified treatment including local ablative techniques or surgical resection remains unclear. Our finding of FGFR alterations in three of four cases indicates a potential role of FGFR signaling in adult pancreatoblastoma whose clinical significance warrants further study.